KUALITAS TIDUR DENGAN PRESTASI AKADEMIK MAHASISWA KEPERAWATAN - Mawu, Rivaldo; Hartono, Theresia; Walansendow, Veronica (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2026)
Introduction: Nursing students often experience poor sleep quality due to high academic demands, which is believed to affect their academic performance. Objective: To identify the relationship between sleep quality and academic performance among fifth-semester students at the Faculty of Nursing, De La Salle Catholic University of Manado. Methods: This study employed a quantitative correlational design with a cross-sectional approach and involved 46 respondents selected through purposive sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while academic performance was assessed based on the Cumulative Grade Point Average (CGPA). Data analysis was performed using Spearman’s Rho test. Results: All respondents (100%) fell into the poor sleep quality category, while the majority had academic performance in the good category. The analysis results showed a correlation coefficient of 0.075 with a p-value greater than 0.05, indicating no significant relationship between sleep quality and academic performance. Conclusion: The academic performance of nursing students is not significantly related to sleep quality and is likely influenced by factors other than sleep patterns.